Structure-property relationship of different types of polyester industrial yarns - Samui, Barun Kumar; Prakasan, Manikanda Priya; Ramesh, C.; Chakrabarty, Debabrata; Mukhopadhyay, R. (Journal of the Textile Institute, 2013)
Four major types of polyester industrial yarns (1000 Denier) which are used commercially were studied for their key structural parameters. An attempt has been made to establish a relationship between morphology and properties of these yarns. High tenacity (HT) polyester yarn has the highest birefringence, amorphous orientation, and long period but is relatively less crystalline. High shrinkage characteristic of HT polyester yarn can be accounted for its higher amorphous orientation. High modulus low shrinkage (HMLS) polyester yarn has higher crystallinity and crystal size compared to HT yarn. Fraction of tie molecules of these yarns has been calculated and found that low shrinkage (LS) and super low shrinkage (SLS) yarns have lesser tie molecules. These LS and SLS yarns are tailor-made to achieve lower shrinkage and at the same time maintaining a good level of tenacity. This is achieved with lower amorphous orientation in the final drawn yarn structure. Amorphous orientation was found to have stronger influence than any other structural parameter on the key yarn properties like modulus, tenacity, elongation, and shrinkage.
Keywords: modulus; orientation; polyester; shrinkage; structure